Qualitative analysis of small animal veterinarian-perceived barriers to nutrition communication - Wenzel, Sophie G; Coe, Jason B; Long, Tara; Koerner, Sydney; Harvey, Morgan; Shepherd, Megan L (Journal of the American Veterinary Medical Association, 2024)
Nutrition is important in preventing and managing disease. Veterinarians are an important source of nutrition information; however, nutrition communication between veterinarians and pet owners is relatively infrequent. The purpose of this study was to conduct a qualitative review of barriers to nutrition communication and possible solutions, reported by small animal veterinarians. 18 veterinarians from Maryland, Michigan, Virginia, Washington DC, and West Virginia. In a qualitative focus group study, 5 virtual focus groups using the Zoom platform were conducted from February 3, 2021, to April 2, 2021. Each focus group was audio recorded, and transcripts were created using Otter.ai software. Transcripts were analyzed in Atlas.ti qualitative data analysis software using a hybrid of inductive and deductive thematic analysis. The 4 barriers to nutrition communication identified by veterinarians were as follows: (1) time, (2) misinformation and information overload, (3) pet owners' apprehension toward new information, and (4) veterinarians' confidence in nutrition knowledge and communication skills. Potential solutions include (1) improving communication and nutrition education, (2) improving and increasing access to client-friendly resources, and (3) empowering credentialed veterinary technicians and support staff to discuss nutrition. This study provides guidance for how to focus efforts to break down barriers to nutrition communication in small animal veterinary practice.